An Integrated Risk Management Framework for Global Supply Chains - Mualla Gonca Avcı (Journal of Advanced Research in Natural and Applied Sciences)
In this study, a risk management framework is developed to support risk management decisions in global supply chains. The proposed framework covers all phases of risk management, namely, risk identification, risk miti-gation and control. In the risk identification phase of the framework, the supply chain is decomposed into either material-level or product-level sub-networks according to the decision maker’s preference. Afterwards, the most crit-ical sub-network is modelled to evaluate different risk mitigation strategies. In particular, a combination of redun-dancy and flexibility strategies is considered for risk mitigation. These strategies are evaluated by simulation models in terms of their effectiveness and efficiency. While inventory holding cost is used as efficiency measure, effective-ness of the strategies is measured by premium freight ratio. The proposed framework provides a comprehensive and reliable decision support since it covers all phases of risk management and relies on quantitative data, and statistical analysis in risk modelling. Moreover, it is flexible as it can be easily adapted to any change in supply chain environ-ment and strategy. In order to show the applicability of the framework, a practical demonstration is presented for a European automotive company. The results indicate that the proposed framework improves the supply chain perfor-mance in terms of efficiency and effectiveness.